PENGARUH AUDIT CLIENT TENURE, AUDIT DELAY, OPINION SHOPPING, DAN PROPORSI KOMISARIS INDEPENDEN TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN REAL ESTATE AND PROPERTY YANG TERDAFTAR DI BEI TAHUN 2007-2012 - Mariani -; Zulbahridar -; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The main purpose of this research is examining and knowing the efffects of audit client tenure, audit delay, opinion shopping, and proportion of independent commissioner on going concern opinion audit. The population in this study were real estate and property firm listing in Indonesia Stock Exchange period 2007-2012, with the population total 78 firms. The sample are taken using purposive sampling method. Type and data source in this study is documentary and secondary data such as annual financial statement and independence auditor report. The logistic regression used to examine the factors that are predicted to affect the probability of acceptance of going concern audit opinion. The result of this research show that audit delay has an effect on going concern opinion audit. Then, audit client tenure, opinion shopping and proportion of independent commissioner does not have significant effect on going concern opinion audit.Keywords: going concern opinion audit, audit client tenure, audit delay, opinion shopping and proportion of independent commissioner.